Anger Makes Us Ugly: Reflections from Pāli Buddhism - Anderson, Carol S. (Buddhist Christian studies, 2019)
This article opens with a personal anecdote with a Buddhist teacher in the late 1980s, in which I ground my reflections on anger. I draw on the teachings about anger in the Pāli Buddhist textual tradition, which are rich with examples of anger, among both lay women, lay men, bhikkhus, and a few remarks about bhikkhunis. The Pāli tradition consistently represents the Buddha as the one who recognizes the causes of anger and abjures his followers to let go of anger, replacing it with loving-kindness—in all situations. The Pāli tradition recognizes the embodied nature of anger, in one sutta, comparing it to inscriptions on a stone that is likened to the human body. In contrast, I explore contemporary discussions of anger in the United States, drawing largely on the work of Martha Nussbaum and others. While contemporary writers frame their discussions of anger in terms of political and social change, this dimension is absent in the Pāli tradition. The article concludes with insights about anger from bell hooks and Anne Klein, who recognize that anger for women of color and white women may be a necessary step toward the establishment of a sense of self, which must be established before one can let it go, in accordance with Buddhist teachings.